A mysterious tale of the Great Cat God and the many serpents. (October 2020) - MacGregor, Gavin
Abstract : An imagined dialogue with Mann through art, conversation and letters. It explores the struggle to make sense of a world that flings events so large, and at times perhaps overwhelming, it is difficult for people to remain anchored.